2009
DOI: 10.1111/j.1530-0277.2008.00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Ethanol Intake in Preadolescent, Adolescent, and Adult Wistar Rats Under Acquisition, Maintenance, and Relapse‐Like Conditions

Abstract: In summary, using a short period of ethanol exposure and a brief deprivation period the results revealed a direct relationship between chronological age and propensity to consume alcohol, being the adolescence a transition period from the infant to the adult pattern of alcohol consumption. Preadolescent animals showed the highest ethanol consumption level. The ADE was only found in adult animals for both alcohol consumption and preference, whereas adolescents showed an ADE only for preference. No effect of sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 22 publications
7
30
0
Order By: Relevance
“…Vetter-O'Hagen et al (2009), using a 2 h limited-access to ethanol model, found that the ethanol consumed varied as a function of sex and age, although the sex differences that emerged at each age were opposites: adolescent males consumed more ethanol than both the adolescent and adult females, while in adulthood, echoing the data in the previous paragraph, the females consumed more ethanol than the males. Nevertheless, it should be noted that not all studies point to these differences in sex, as in the findings obtained by García-Burgos et al (2009), using a 24 h unlimited-access to ethanol model. While their results do seem to indicate a greater consumption of ethanol in adolescent rats, they suggested no difference by sex.…”
Section: Introductionmentioning
confidence: 85%
“…Vetter-O'Hagen et al (2009), using a 2 h limited-access to ethanol model, found that the ethanol consumed varied as a function of sex and age, although the sex differences that emerged at each age were opposites: adolescent males consumed more ethanol than both the adolescent and adult females, while in adulthood, echoing the data in the previous paragraph, the females consumed more ethanol than the males. Nevertheless, it should be noted that not all studies point to these differences in sex, as in the findings obtained by García-Burgos et al (2009), using a 24 h unlimited-access to ethanol model. While their results do seem to indicate a greater consumption of ethanol in adolescent rats, they suggested no difference by sex.…”
Section: Introductionmentioning
confidence: 85%
“…The neglect of adolescence, in rodents ranging approximately from 3 to 7 weeks of age (Adriani et al 2002;Laviola et al 2003;Spear 2000), is especially surprising, given the demonstrated relevance of this phase in the development of a number of neuropsychiatric pathologies (Paus et al 2008). For example, adolescents have a marked propensity to develop risk-and drug-taking behaviors and this propensity also appears in rat (Doremus-Fitzwater and Spear 2007;Garcia-Burgos et al 2009;Maldonado et al 2008;Ristuccia and Spear 2008;Varlinskaya and Spear 2004a, b) and mouse (Hefner and Holmes 2007;Itzhak and Anderson 2008;Linsenbardt et al 2008;Stevenson et al 2008;Tambour et al 2008) models. In addition, different psychopharmacological profiles have been described between the pre-pubertal/early (*4 weeks), peri-adolescent (*6 weeks), and adult stages (Adriani et al 2002;Laviola et al 2003;Spear 2000;Spear and Brake 1983).…”
Section: Introductionmentioning
confidence: 93%
“…Rat alcohol consumption peaks at night in a light/dark cycle [111]. In mice, alcohol is more intoxicating at night than during the day, and genetic knockout of Per2 eliminates this differential sensitivity, leading to overall increases in alcohol intake across the 24 hr cycle [112].…”
mentioning
confidence: 99%